A procedural perspective on academic spin-off creation: the changing relative importance of the academic and the commercial sphere - Uwe Cantner; Philip Doerr; Maximilian Goethner; Matthias Huegel; Martin Kalthaus (Small Business Economics, 2023)
Academic scientists who commercialize their research findings via spin-off creation have to transition from the academic sphere to the commercial sphere. Along this spin-off creation process, they face challenges adapting to the conflicting logics of these spheres.~We hypothesize that throughout the three phases of this process, the importance of the academic sphere decreases while the importance of the commercial sphere increases. We collected a representative sample of 1,149 scientists from the German state of Thuringia. To test our hypotheses, we apply dominance analysis and estimate the relative importance of the two spheres. In line with our hypotheses, the importance of the academic sphere declines and the importance of the commercial sphere increases at the beginning of the process. Towards the end of the process, we observe a further decline in the relative importance of the academic sphere, but, unexpectedly, also a decline for the commercial sphere. Notably, our results show that the commercial sphere is in general more important than the academic sphere throughout the process. Our results challenge existing conceptualizations that emphasize the importance of the academic sphere, especially at the beginning of the spin-off founding process. The results provide intervention points for policy measures to promote academic spin-offs.
Keywords: L26; O31; O33; 330; Academic spin-off; Conflicting logics; Process perspective; Phase model; Dominance analysis